Meningkatkan Kehandalan Safety dengan Menciptakan Alat Coupling Spool Pieces di Conventional Buoy Mooring IT Ampenan - Oscar Adhi Wicaksono; Lutfi Bahroni (Publikasi Indonesia, 2022)
Hose connect/disconnect activities to Manifold Tankers in the CBM area have a very high risk (spill overboard, fire, etc.). Therefore, one of the things that can be used as a solution is to create a tool called a Coupling Spool Piece which is made of stainless steel which is anti-rust, seawater resistant, not easily broken, and non-welded. It is designed with an ergonomic size and can be used as a rope tie hook. So that with the solution created, it is hoped that the quality of materials and materials will be more reliable and safety, save costs because they have succeeded in preventing fuel spills and reducing operational losses as well as the effectiveness of tanker operations, and can improve operational safety reliability